Análisis sobre el poder de mercado del sector eléctrico colombiano (2016)
In this paper document a re calculated measures of market power and it examine the bidding behavior of the most important firms i n the Colombian electricity market. The sensitivity of the marginal cost for each firm was estimated to evaluate shocks the elasticity of the series to fuel prices and water resources. . The motivation is to discuss the possible existence of non - competitive behaviors from the pivotal generators to supply the market at peak hours and consequent market inefficiencies. Based on data released by XM. The resu lts suggest that between 2001 and 2014 the spot price is less sensitive to exogenous shocks than the marginal costs of firms. Therefore, it has concluded that the system works relatively well against exogenous shocks in production inputs . However, there ar e conditions for the exercise of market power.